Las relaciones de poder como elemento constitutivo del delito de femicidio en el Código Orgánico Integral Penal - Miranda Nájera, Adriana Alexandra (2018)
Nowadays, the femicide crime has become a real ordeal to prove power relation as an element of the typical behavior of the offense in which women are killed for reasons of gender. Through a qualitative approach, systematic and methodological process; and, with the application of the inductive, analytical and descriptive methods, it has been possible to determine several forms of power relations as constitutive elements of the FEMICIDE crime. Gender power relations are not individual behaviors but rather a social structure based on differences between sexes and inequality in relation to the assignment of historical roles. It is made up by actions of imposition, force, supremacy, authority; and domination; in the following areas: social, familiar, cultural, economic, labor, educational, religious, sexual, access to justice, symbolic, among others; resulting in the justice system of the province of Chimborazo: gaps, ignorance and prejudices by some operators of justice at the moment of dealing with crimes of gender violence including femicide; within the motivations, neither the conceptualization of power relations are not clearly determined, nor how it influenced the concrete case subjected to judgment. The government’s commitment to provide specialized training courses on the subject is relevant; and, an adequate definition of the legal standard in which the forms of power relations are clearly included and determined. Within the present research, the doctrinal, legal and jurisprudential concepts are offered, the contribute to define, understand and determine power relations, providing a contribution to academia and citizens in general, and who through their critical viewpoint can make their determinations.